PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP KINERJA SKPD PEMERINTAH DI KABUPATEN KEPULAUAN SANGIHE - Maindoka, Deifi Sari; Wokas, Heince (Universitas Sam Ratulangi, 2013)
Budget is needed to reveal what it will doin the future. Budgets are usually only focused for a certain period or a period of 1year. With a good budget, can be easily obtained information in decision-making. Therefore, it is necessary to havean effective budget allocation to balance the various demands in achieving the desired objectives.The objectives of this research was todetermine the effect of the application of performance-based budgeting to performance work unit in the islands of Sangihe regency government. The research was done by conducting a survey to the Echelon II and Echelon III and data collection is done by distributing questionnaires to 60 respondents.The analytical method used is simple line arregression analysis, and hypothesis testing is used for testing statisticalt-test. With the help of a computer software program SPSS Version 2.0 for windows. Simple line arregression analysis results obtaine dequation Y=5,134+0.748X. coefficient for variable X ( Performance-based budgeting) ) is equal to the positive ( 0.748) , this means that the variable performance-based budgeting or direct positive effecton the variable Y ( Performance on education ) . The contribution of performance-based budgeting to the rise and fall of variation of performance variables on education goverment in Sangihe regency indicated by the coefficient of determination of 57.3% while the remaining 43.7% is explained by other factors not examined in this study include reporting information system finance.